News & Views: A trinagular affair - Engel, Michael; Glotzer, Sharon C. (Nature Physics, 2014)
Disks interacting via particular potentials self-organize into triangles that stabilize mosaics with 10-, 12-, 18- and 24-fold symmetry, as revealed by computer simulations. Discoveries of further novel quasicrystals may now be within reach.